An ecosystem-wide reproductive failure with more snow in the Arctic - Schmidt, Niels Martin; Reneerkens, Jeroen; Christensen, Jens Hesselbjerg; Olesen, Martin; Roslin, Tomas (PLOS Biology, 2019)
2018: Arctic researchers have just witnessed another extreme summer—but in a new sense of the word. Although public interest has long been focused on general warming trends and trends towards a lower sea ice cover in the Arctic Ocean, this summer saw the realization of another predicted trend: that of increasing precipitation during the winter months and of increased year-to-year variability. In a well-studied ecosystem in Northeast Greenland, this resulted in the most complete reproductive failure encountered in the terrestrial ecosystem during more than two decades of monitoring: only a few animals and plants were able to reproduce because of abundant and late melting snow. These observations, we suggest, should open our eyes to potentially drastic consequences of predicted changes in both the mean and the variability of arctic climate.